2014
DOI: 10.1371/journal.pone.0086626
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cystoid Change Phenotypes in Ocular Toxoplasmosis Using Optical Coherence Tomography

Abstract: PurposeTo present unique cystoid changes occurring in patients with ocular toxoplasmosis observed in spectral domain optical coherence tomography (OCT).MethodsForty-six patients (80 eyes) with a diagnosis of ocular toxoplasmosis, who underwent volume OCT examination between January 2005 and October 2012, were retrospectively collected. Review of clinical examination findings, fundus photographs, fluorescein angiograms (FA) and OCT image sets obtained at initial visits and follow-up. Qualitative and quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Cystic spaces within the retina were previously described in a large cohort of patients with intraocular toxoplasmosis. In this study, cystoid degeneration was identified in 15% of the patients and cystoid macular oedema (CME) in 7.5% 10. Our study confirms that cystoid degeneration is common in toxoplasmic retinochoroiditis, but a similar percentage of patients with viral retinitis had lacunae in the ONL.…”
Section: Discussionsupporting
confidence: 79%
“…Cystic spaces within the retina were previously described in a large cohort of patients with intraocular toxoplasmosis. In this study, cystoid degeneration was identified in 15% of the patients and cystoid macular oedema (CME) in 7.5% 10. Our study confirms that cystoid degeneration is common in toxoplasmic retinochoroiditis, but a similar percentage of patients with viral retinitis had lacunae in the ONL.…”
Section: Discussionsupporting
confidence: 79%
“…These parameters can be more reliable than the visual acuity in assessing response to intervention [ 11 ] . Widespread availability of spectral domain OCT (SD-OCT) has provided improved visualization of the details of the neurosensory retina and has facilitated the detection of many retinal/choroidal abnormalities, including cystoid lesions in OT and SRF [ 10 , 12 , 13 ] . The purpose of the current study is to report the observation of SRF in patients with active OT, and to investigate its associate clinical course and therapeutic consequences.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study of 926 patients with active ocular toxoplasmosis, 49 (5.0%) patients presented optic disc swelling, and this was most frequently found in association with an active distant focus of retinochoroiditis (11) . Macular serous retinal detachment and cystoid changes have also been described in patients with toxoplasmic retinochoroiditis not involving zone 1 (16,17) . Vitreous inflammation secondary to retinochoroiditis can also induce vitreous haze and di sorders of the vitreoretinal interface.…”
Section: Discussionmentioning
confidence: 93%